2008
DOI: 10.1521/psyc.2008.71.4.339
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health Consequences of Disaster-Related Loss: Findings from Primary Care One Year After the 9/11 Terrorist Attacks

Abstract: This study examines the long-term psychiatric consequences, pain interference in daily activities, work loss, and functional impairment associated with 9/11-related loss among low-income, minority primary care patients in New York City. A systematic sample of 929 adult patients completed a survey that included a sociodemographic questionnaire, the PTSD Checklist, the PRIME-MD Patient Health Questionnaire, and the Medical Outcomes Study Short Form-12 (SF-12).Approximately one-quarter of the sample reported know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 28 publications
5
48
0
1
Order By: Relevance
“…The majority of previous studies explored the risk factors of PTSD largely in isolation from other putative risk factors, such as sleep problems [18,19] and somatic discomforts, [20,21] which have been well-documented. Everyday functional impairment was also found to be related to psychological trauma, [22,23] because small changes of everyday functioning can be predictive of an increased risk for future pathologic behavior and be a source of psychological distress. [24,25] To our knowledge, there is no study included all the aforementioned variables to explore the risk factors of PTSD, let alone in teachers.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of previous studies explored the risk factors of PTSD largely in isolation from other putative risk factors, such as sleep problems [18,19] and somatic discomforts, [20,21] which have been well-documented. Everyday functional impairment was also found to be related to psychological trauma, [22,23] because small changes of everyday functioning can be predictive of an increased risk for future pathologic behavior and be a source of psychological distress. [24,25] To our knowledge, there is no study included all the aforementioned variables to explore the risk factors of PTSD, let alone in teachers.…”
Section: Introductionmentioning
confidence: 99%
“…[1] High prevalence of posttraumatic stress disorder (PTSD) and depression (major depressive disorder, MDD) has been reported in disaster bereaved. [2,3] Recently, some studies have shown that disaster deaths can be followed by prolonged grief disorder (PGD) in a substantial number of bereaved. [4][5][6] PGD (also referred to as complicated or traumatic grief) is considered a mental health disorder proposed for DSM-V and ICD-11, and consists of symptoms such as severe yearning for the deceased, difficulties accepting the loss, bitterness or anger related to the loss ongoing for at least 6 months after the death.…”
Section: Introductionmentioning
confidence: 99%
“…Most work has been done on the impact of disasters on survivors [72][73][74][75]. Some work has begun to differentiate the special needs of particular populations, for example children [76][77][78].…”
Section: Recovery and Longer Term Psychosocial Effectsmentioning
confidence: 99%